Optimising the method to develop spheroids from MDA-MB-468 human triple negative breast cancer cells - Shaza M. Mohamedahmed; Muhamad Noor Alfarizal Kamarudin; Premdass Ramdas; Usha Sundralingam; Ammu K. Radhakrishnan (Molecular Biology Reports, 2026)
Purpose Three-dimensional (3D) spheroid models are increasingly used to emulate the tumour microenvironment for preclinical drug screening. This study aimed to optimise and assess spheroid formation from MDA-MB-468 triple-negative breast cancer (TNBC) cells using hanging drop, liquid overlay, and rigid scaffold methods under normal oxygen (NOC) and low oxygen (LOC) culture conditions. Methods Spheroids were generated and characterised using bright-field microscopy with AnaSP morphometrics (sphericity, solidity, and perimeter). Gene expression of Epithelial-Mesenchymal Transition (EMT), stemness, and hypoxia/angiogenesis markers (CD44, HIF1A, VEGFA, TWIST1, SNAI1, and NES) was quantified using qPCR. The optimised model was further evaluated using field-emission scanning electron microscopy (FE-SEM) and Hoechst fluorescence. Results A workflow combining hanging-drop pre-aggregation with ultra-low attachment (ULA) or agarose-coated plates under NOC produced consistent, compact spheroids. Scaffold cultures formed rapidly but showed size variability under NOC and LOC. Across methods, spheroids were less compact, and gene expression patterns deviated from expected hypoxic responses. HIF1A and VEGFA were more highly expressed under NOC, suggesting pseudo-hypoxic signalling and activation of angiogenesis-related pathways. CD44 and TWIST1 were upregulated in most spheroid types, whereas SNAI1 and NES exhibited condition- and method-specific variability. Conclusion Spheroids cultivated under normoxic conditions demonstrated enhanced structural integrity and transcriptional fidelity. Nonetheless, the study identified that the most compact and resilient spheroids were achieved through the use of hanging-drop pre-aggregation combined with ULA-plates under NOC. The enhanced structural integrity and transcriptional fidelity observed in these spheroids make them valuable models for studying cancer biology and drug responses.

Molecular diversity of Tamarindus indica clones using Inter Simple Sequence Repeat (ISSR) Markers - Mayavel A; Amaravel M; Akshayasri M; Andrew Peter Leon M.T; Maheswari Patturaj; Sindhu Agasthikumar; Bagathsingh C; Radhakrishnan G; Binai Nagarajan (Tropical Plant Biology, 2026)

Trends in extreme climate indices of the Amaravathi Basin, India: a spatiotemporal analysis - M Jothi Jeya Sri; Nisha Radhakrishnan; Aneesh Mathew; Surendar Natarajan (Journal of Earth System Science, 2026)

Myelin oligodendrocyte glycoprotein antibody disease (MOGAD) with leukodystrophy-like presentation in an adult - Sreeja Samineni; Divya M. Radhakrishnan; Ajay Garg; Divyani Garg; Ayush Agarwal (Acta Neurologica Belgica, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Endophytic Xylaria sp. enhances tolerance in rice to bacterial leaf blight and promotes growth - K. Sushitha; A. Sajeena; N. V. Radhakrishnan; M. Joy; Jacob John; Swapna Alex; R. Beena (European Journal of Plant Pathology, 2025)

Novel o-Terphenyl Luminophores for Optoelectronic Devices: Synthesis, Photophysical, Electrochemical, and Thermal Analysis - Amarsinh R. Mainak; Pranjali S. Kewate; Vasanti B. Shabade; Vishnu V. Kutwade; Radhakrishnan M. Tigote; Netaji K. Desai; Sidram R. Pujari (Journal of Fluorescence, 2025)

First report of stem canker disease caused by Neoscytalidium lignicola on dragon fruit in Kerala - Kovvuri Janakadatta Reddy; M. K. Dhanya; R. Ayisha; A. Sajeena; N. V. Radhakrishnan (Indian Phytopathology, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Sensitivity, criticality, and optimization in bipartite networks: application in urban transit infrastructure - Claudio M. Rocco; Kash Barker; Sridhar Radhakrishnan; Jose Moronta (Environment Systems and Decisions, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Target, suspect, and non-target analysis of halogenated organic pollutants in spotted seals (Phoca largha) from Peter the Great Bay, East Sea/Sea of Japan - Sori Mok; Aiswarya Radhakrishnan; Thi Thu Trang Nguyen; Junseong Park; Alexey M. Trukhin; Moonjin Lee; Hyo-Bang Moon (Marine Pollution Bulletin, 2025)

Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Novel in-genome based analysis demonstrates the evolution of OmpK37, antimicrobial resistance gene from a potentially pathogenic pandrug resistant Klebsiella pneumoniae MS1 isolated from healthy broiler feces - Sreejith Sreekumaran; Priya V K; Manjusha Premnath; Prathiush P R; Anisha M N; Jyothis Mathew; Jayachandran K; Radhakrishnan E K (Science of The Total Environment, 2024)

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Hanging in the air: tree moss diatoms from Indo-Burma biodiversity hot spot of India - C. Radhakrishnan; M. Yogeshwaran; B. Karthick (Aerobiologia, 2022)

Three territory sign in COVID-19 - Prashant Bhatele; Animesh Das; Awadh Kishor Pandit; Divya M. Radhakrishnan; Achal Kumar Srivastava (Acta Neurologica Belgica, 2022)

Mesenchymal Stem Cell Therapy in the Treatment of Neurodegenerative Cerebellar Ataxias: a Systematic Review and Meta-analysis - Manish Bhartiya; Amit Kumar; Rakesh K. Singh; Divya M Radhakrishnan; Roopa Rajan; Achal Kumar Srivastava (The Cerebellum, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Altered functional network connectivity and working memory dysfunction in adolescents with epilepsy - Jennifer Vannest; Rupa Radhakrishnan; Ana M. Gutierrez-Colina; Shari L. Wade; Thomas Maloney; Angela Combs; Luke Turnier; Shelby Merder; Mekibib Altaye; Tzipi-Horowitz-Kraus; Avani C. Modi (Brain Imaging and Behavior, 2021)

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Genome-based trait prediction in multi- environment breeding trials in groundnut - Manish K. Pandey; Sunil Chaudhari; Diego Jarquin; Pasupuleti Janila; Jose Crossa; Sudam C. Patil; Subramaniam Sundravadana; Dhirendra Khare; Ramesh S. Bhat; Thankappan Radhakrishnan; John M. Hickey; Rajeev K. Varshney (Theoretical and Applied Genetics, 2020)
Key message Comparative assessment identified naïve interaction model, and naïve and informed interaction GS models suitable for achieving higher prediction accuracy in groundnut keeping in mind the high genotype × environment interaction for complex traits. Abstract Genomic selection (GS) can be an efficient and cost-effective breeding approach which captures both small- and large-effect genetic factors and therefore promises to achieve higher genetic gains for complex traits such as yield and oil content in groundnut. A training population was constituted with 340 elite lines followed by genotyping with 58 K ‘Axiom_Arachis’ SNP array and phenotyping for key agronomic traits at three locations in India. Four GS models were tested using three different random cross-validation schemes (CV0, CV1 and CV2). These models are: (1) model 1 (M1 = E + L) which includes the main effects of environment (E) and line (L); (2) model 2 (M2 = E + L + G) which includes the main effects of markers (G) in addition to E and L; (3) model 3 (M3 = E + L + G + GE), a naïve interaction model; and (4) model 4 (E + L + G + LE + GE), a naïve and informed interaction model. Prediction accuracy estimated for four models indicated clear advantage of the inclusion of marker information which was reflected in better prediction accuracy achieved with models M2, M3 and M4 as compared to M1 model. High prediction accuracies (> 0.600) were observed for days to 50% flowering, days to maturity, hundred seed weight, oleic acid, rust@90 days, rust@105 days and late leaf spot@90 days, while medium prediction accuracies (0.400–0.600) were obtained for pods/plant, shelling %, and total yield/plant. Assessment of comparative prediction accuracy for different GS models to perform selection for untested genotypes, and unobserved and unevaluated environments provided greater insights on potential application of GS breeding in groundnut.

Correction to: Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Tenecteplase versus alteplase in acute ischemic stroke: systematic review and meta-analysis - A. Thelengana; Divya M. Radhakrishnan; Manya Prasad; Amit Kumar; Kameshwar Prasad (Acta Neurologica Belgica, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Coping capacities for improving adaptation pathways for flood protection in Can Tho, Vietnam - Mohanasundar Radhakrishnan; Hong Quan Nguyen; Berry Gersonius; Assela Pathirana; Ky Quang Vinh; Richard M. Ashley; Chris Zevenbergen (Climatic Change, 2018)

Design of novel amyloid β aggregation inhibitors using QSAR, pharmacophore modeling, molecular docking and ADME prediction - Lilly Aswathy; Radhakrishnan S. Jisha; Vijay H. Masand; Jayant M. Gajbhiye; Indira G. Shibi (In Silico Pharmacology, 2018)

Phytochemical constituents and antioxidant activity of Echinops albicaulis - Lashyn Kiyekbayeva; Nesma M. Mohamed; Orazbekov Yerkebulan; Enas I. Mohamed; Datkhayev Ubaidilla; Akhtayeva Nursulu; Mamurova Assem; Radhakrishnan Srivedavyasasri; Samir A. Ross (Natural Product Research, 2018)

Culturable Endophytic Bacteria of Ginger Rhizome and their Remarkable Multi-trait Plant Growth-Promoting Features - Sabu Rohini; R. Aswani; M. Kannan; V. P. Sylas; E. K. Radhakrishnan (Current Microbiology, 2018)

Photochemical Degradation of Curcumin: a Mechanism for Aqueous Based Sensing of Fluoride - Roopa Venkataraj; C. P. Girijavallabhan; P. Radhakrishnan; V. P. N. Nampoori; M. Kailasnath (Journal of Fluorescence, 2017)

Exploration of 3,6-dihydroimidazo(4,5-d)pyrrolo(2,3-b)pyridin-2(1H)-one derivatives as JAK inhibitors using various in silico techniques - Radhakrishnan S. Jisha; Lilly Aswathy; Vijay H. Masand; Jayant M. Gajbhiye; Indira G. Shibi (In Silico Pharmacology, 2017)

Suppression of Baseline Wander Artifact in Magnetocardiogram Using Breathing Sensor - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)

Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)
Electroencephalography (EEG) is a non-invasive way of recording brain activities, making it useful for diagnosing various neurological disorders. However, artifact signals associated with eye blinks or the heart spread across the scalp, contaminating EEG recordings and making EEG data analysis difficult. To solve this problem, we implement a common methodology to suppress both cardiac and ocular artifact signal, by correlating the measured contaminated EEG signals with the clean reference electro-oculography (EOG) and electrocardiography (EKG) data and subtracting the scaled EOG and EKG from the contaminated EEG recording. In the proposed methodology, the clean EOG and EKG signals are extracted by subjecting the raw reference time-series data to ensemble empirical mode decomposition to obtain the intrinsic mode functions. Then, an unsupervised technique is used to capture the artifact components. We compare the distortion introduced into the brain signal after artifact suppression using the proposed method with those obtained using conventional regression alone and with a wavelet-based approach. The results show that the proposed method outperforms the other techniques, with an additional advantage of being a common methodology for the suppression of two types of artifact.

Distinct Bacterial Communities Associated with the Coral Model Aiptasia in Aposymbiotic and Symbiotic States with Symbiodinium - Till Röthig; Rúben M. Costa; Fabia Simona; Sebastian Baumgarten; Ana F. Torres; Anand Radhakrishnan; Manuel Aranda; Christian R. Voolstra (Frontiers in Marine Science, 2016)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Mathematical Simulation of Membrane Protein Clustering for Efficient Signal Transduction - Krishnan Radhakrishnan; Ádám Halász; Meghan M. McCabe; Jeremy S. Edwards; Bridget S. Wilson (Annals of Biomedical Engineering, 2012)

Responses to Achilles tendon vibration during self-paced, visually and auditory-guided periodic sway - Saritha M. Radhakrishnan; Vassilia Hatzitaki; Dimitrios Patikas; Ioannis G. Amiridis (Experimental Brain Research, 2011)

Low-frequency internal waves and their influence on transmission loss variability - P. V. Hareesh Kumar; A. Raghunadha Rao; K. Anilkumar; M. Padmanabham; K. G. Radhakrishnan (Natural Hazards, 2011)

Study of changes in bacterial and viral abundance in formaldehyde-fixed water samples by epifluorescence microscopy - Ammini Parvathi; Seetha Radhakrishnan; M. P. Sajila; Breezy Jacob (Environmental Monitoring and Assessment, 2011)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Mulberry biodiversity conservation through cryopreservation - Ananda Rao Atmakuri; Rekha Chaudhury; S. K. Malik; Suseel Kumar; Radhakrishnan Ramachandran; S. M. H. Qadri (In Vitro Cellular & Developmental Biology - Plant, 2009)

Analysis of diallel cross for some physical-quality traits in peanut (Arachis hypogaea L.) - K. Hariprasanna; Chuni Lal; T. Radhakrishnan; H. K. Gor; B. M. Chikani (Euphytica, 2008)

Brain tissue phantoms for optical near infrared imaging - K. Prahlad Rao; S. Radhakrishnan; M. Ramasubba Reddy (Experimental Brain Research, 2006)

Catalase: A repertoire of unusual features - Prashen Chelikani; T. Ramana; T. M. Radhakrishnan (Indian Journal of Clinical Biochemistry, 2005)

Status of the major lobster fisheries in India - E.V. Radhakrishnan; V.D. Deshmukh; Mary K. Manisseri; M. Rajamani; Joe K. Kizhakudan; R. Thangaraja (New Zealand Journal of Marine and Freshwater Research, 2005)
Commercial exploitation of lobsters from the Indian seas began in the 1950s. Annual landings have been declining from a peak of 4075 t in 1985 to 1364 t in 2002. Major fisheries were located on the north‐west, south‐west, and south‐east coasts. Among the 12 species recorded, only four species of spiny lobsters (three littoral and one deep sea) and one species of slipper lobster are commercially important. At Kayalpattinam and Tharuvaikulam, on the south‐east coast, lobster landings sharply declined for the gill‐net fishery. Of the two species that contributed to the fishery, Panulirus ornatus and Panulirus homarus, the latter has been more affected owing to high vulnerability to fishing activities. Catch composition analysis of the trammel‐net fishery showed that 35% of the landings consisted of P. homarus in the size range of 23–50 mm carapace length. On the north‐west coast, the spiny lobster Panulirus polyphagus and the slipper lobster Thenus orientalis are incidentally caught in trawl nets. However, the fishery for T. orientalis in the waters off Mumbai lasted only up to 1994. Large‐scale exploitation of spawning females, which formed 60% of the total catch, might have been detrimental to the recruitment process resulting in rapid decline and total collapse of the fishery. Abundance of P. polyphagus reached its maximum during September, constituting 23% of the average annual landing during 1988–2002. A high exploitation ratio (>0.7) indicated over‐fishing of the stock. Repeated spawning and high annual egg production are probably responsible for sustaining the stock, despite over‐exploitation. Major problems confronting the resource management of the multi‐gear and multi‐species lobster fisheries in India are discussed. An operational project, involving fisher community, has been taken up for creating awareness of the need for sustainable exploitation of the resource. Regulatory measures, such as closure of the fishery during the peak of the breeding season, ban on trammel‐net, mandatory release of egg‐bearing lobsters, and establishment of lobster sanctuaries are suggested to the State Governments for implementation.

Three-dimensional stress analysis for the mechanics of plantar ulcers in diabetic neuropathy - V. J. Thomas; K. M. Patil; S. Radhakrishnan (Medical & Biological Engineering & Computing, 2004)

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)

Enteromorpha compressa (L.) Greville an edible green alga as a source of antiallergic principle (S) - B. Venkata Raman; D. N. Rao; T. M. Radhakrishnan (Indian Journal of Clinical Biochemistry, 2004)

Genetic association analysis of KCNQ3 and juvenile myoclonic epilepsy in a South Indian population - J. Vijai; A. Kapoor; H. M. Ravishankar; P. J. Cherian; A. S. Girija; B. Rajendran; G. Rangan; S. Jayalakshmi; S. Mohandas; K. Radhakrishnan; A. Anand (Human Genetics, 2003)

Absence ofGABRA1 Ala322Asp mutation in juvenile myoclonic epilepsy families from India - A. Kapoor; J. Vijai; H. M. Ravishankar; P. Satishchandra; K. Radhakrishnan; A. Anand (Journal of Genetics, 2003)